2023
DOI: 10.1590/1980-220x-reeusp-2022-0309en
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke mortality and time for hospital arrival: analysis of the first 90 days

Abstract: Objective: To analyze the association between time of arrival at a reference hospital and mortality of people with ischemic stroke. Method: Descriptive and inferential statistics were used. Modifying and confounding variables between time of arrival and mortality were observed in the multivariate analysis. The Akaike Information Criterion was used to choose the model. Statistical significance of 5% and risk correction using the Poisson Model were adopted. Results: Most participants arrived within 4.5 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
1
0
1
Order By: Relevance
“…Individuals aged 45-65 and over 65years showed substantially higher hazard ratios compared to those below 45 years. This also aligns with existing studies (5)(6), emphasizing the impact of age on stroke outcomes and reinforces the important need for tailored care strategies that consider the unique needs and challenges associated with different age groups. Tailoring interventions based on age-specific considerations may enhance the effectiveness of stroke care and improve overall survival rates.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Individuals aged 45-65 and over 65years showed substantially higher hazard ratios compared to those below 45 years. This also aligns with existing studies (5)(6), emphasizing the impact of age on stroke outcomes and reinforces the important need for tailored care strategies that consider the unique needs and challenges associated with different age groups. Tailoring interventions based on age-specific considerations may enhance the effectiveness of stroke care and improve overall survival rates.…”
Section: Discussionsupporting
confidence: 80%
“…These complexities necessitate the need to understand factors influencing survival outcomes, thus providing a foundation for targeted interventions tailored to the unique socio-economic and healthcare landscape. Age consistently emerges as a pivotal factor influencing stroke outcomes, with individuals over 65 years facing a higher risk of death (5)(6). Furthermore, other studies highlighted the predictive role of old age in stroke incidence, emphasizing the importance of age-related considerations (7) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our results are in line with the research conducted by Kortazar-Zubizarreta et al, who conducted a similar study in a single center and reported that a high NIHSS score was one of the main independent predictors of early mortality in ischemic stroke patients [ 26 ]. These findings were further supported by the study conducted by Moraes et al, which showed that a high NIHSS score at admission was significantly associated with early mortality in both ischemic and hemorrhagic stroke patients [ 27 ]. Furthermore, our study contributes to the existing body of literature by demonstrating the prognostic value of the NIHSS score in predicting early mortality in stroke patients.…”
Section: Discussionsupporting
confidence: 61%
“…По данным разных авторов доля недифференцированных инсультов составляла от 18,7% до 29,0%. Недавно была сформирована новая клиническая концепция о том, что большинство кри птогенных инсультов имеют эмболическую этиологию, и было предложено определение эмболическо го инсульта неопределенной этиологии [19,20,22].…”
Section: результаты и их обсуждениеunclassified